The Characteristics of the Influenza Virus Epidemic Around the SARS-CoV-2 Epidemic Period in the Pudong New Area of Shanghai - Ge Zhang; Anran Zhang; Li Zhang; Aiqin Zhu; Zhongjie Li; Weiping Zhu; Wenbiao Hu; Chuchu Ye (Springer, 2024)
Abstract Objectives The concurrent impact of COVID-19 and influenza on disease burden is a topic of great concern. This discussion delves into the epidemiological characteristics of seasonal influenza activity in Shanghai within the context of the SARS-CoV-2 epidemic. Methods From 2017 to 2023, a total of 11,081 patients having influenza-like illness (ILI) were included in this study for influenza virus detection. Reverse transcription polymerase chain reaction (RT-PCR) assays were conducted according to standardised protocols to identify the types and subtypes of influenza viruses. The positivity rate of the influenza virus among the sampled ILI cases served as a surrogate measure for estimating various influenza seasonal characteristics, such as periodicity, duration, peak occurrences, and the prevalent subtypes or lineages. Epidemiological aspects across different years and age groups were subjected to comprehensive analysis. For categorical variables, the Chi-square test or Fisher's exact test was employed, as deemed appropriate. Results A total of 1553 (14.0%) tested positive for influenza virus pathogens. The highest positivity rate for influenza was observed in adults aged 25-59 years (18.8%), while the lowest rate was recorded in children under 5 years (3.8%). The influenza circulation patterns in Shanghai were characterised: (1) 2 years exhibited semiannual periodicity (2017-2018, 2022-2023); (2) 3 years displayed annual periodicity (2018-2019, 2019-2020, and 2021-2022); and (3) during 2020-2021, epidemic periodicities of seasonal influenza viruses disappeared. In terms of influenza subtypes, four subtypes were identified during 2017-2018. In 2018-2019 and 2019-2020, A/H3N2, A/H1N1, and B/Victoria were circulating. Notably, one case of B/Victoria was detected in 2020-2021. The epidemic period of 2021-2022 was attributed to B/Victoria, and during 2022-2023, the influenza A virus was the dominant circulating strain. Conclusions The seasonal epidemic period and the predominant subtype/lineage of influenza viruses around the SARS-CoV-2 epidemic period in Shanghai city are complex. This underscores the necessity for vigilant influenza control strategies amidst the backdrop of other respiratory virus pandemics.